2013
DOI: 10.1111/cdev.12066
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Mediation: Cumulative Contextual Risk, Maternal Differential Treatment, and Children's Behavior Within Families

Abstract: This study tests the hypothesis that links between contextual risk and children's outcomes are partially explained by differential parenting. Using multi-informant measurement and including up to four children per family (Mage  = 3.51, SD = 2.38) in a sample of 397 families, indirect effects (through maternal differential parenting: self-reported and observed) of cumulative contextual risk on four child outcomes were investigated. Cumulative risk was associated with higher levels of differential parenting and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(117 citation statements)
references
References 118 publications
(126 reference statements)
5
107
0
5
Order By: Relevance
“…The present findings replicate previous research showing an association between cumulative risk exposure and engagement in maladaptive coping (Leitenberg, Gibson, & Novy, 2004), and also contributes to the literature by showing this association in a population whose coping strategies in the context of cumulative risk have been under-studied. The findings also support those of prior studies showing detrimental effects of cumulative risk on child outcomes through either direct or indirect links (Buehler & Gerard; 2013; Meunier et al, 2013). …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present findings replicate previous research showing an association between cumulative risk exposure and engagement in maladaptive coping (Leitenberg, Gibson, & Novy, 2004), and also contributes to the literature by showing this association in a population whose coping strategies in the context of cumulative risk have been under-studied. The findings also support those of prior studies showing detrimental effects of cumulative risk on child outcomes through either direct or indirect links (Buehler & Gerard; 2013; Meunier et al, 2013). …”
Section: Discussionsupporting
confidence: 89%
“…Following prior studies (Buehler & Gerard, 2013; Meunier, Boyle, O'Connor, & Jenkins, 2013), in order not to mask the unique contribution of each individual risk factor, supplemental analyses were performed to examine the association between each individual risk factor, coping and problem behaviors. Regression analyses were performed using individual risk factors as predictors of behavior problems and each dimension of coping.…”
Section: Resultsmentioning
confidence: 99%
“…In general, studies on the moderation of cognitive development by environmental factors have focused on the associations between child poverty and accumulation of risk factors (Gassman-Pines and Yoshikawa, 2006; Weiland and Yoshikawa, 2012; Flouri et al, 2013; Meunier et al, 2013). Less analytical efforts have been devoted to moderation based on risk factors in the area of intervention science.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies found that differential parenting leads to less compliance and prosocial behavior, and more externalizing behavior in the less favored sibling, although there is also some evidence that it may lead to more prosocial behavior in the less favored sibling (Knafo 2009). Differential parenting has also been related to more social problems in both siblings, the favored as well as less favored (Meunier et al 2013). In early childhood, sharing with siblings and compliance are central aspects of social development within the family context (Knafo and Plomin 2006;Kochanska and Aksan 2006), so differential sensitivity during toddlerhood may be especially relevant for the development of these behaviors.…”
Section: Introductionmentioning
confidence: 99%